The Use of Social Networks Sites as Teaching Media in Facilitating English Writing Lesson in Senior High Schools and Vocational High Schools in Buleleng - ., Yeyen Andiani; ., Made Hery Santosa, S.Pd, M.Pd.; ., I Putu Indra Kusuma, S.Pd., M.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2016)
Social networks sites adalah online platform yang dapat digunakan untuk mendukung proses belajar mengajar di era global ini. Penelitian ini bertujuan untuk mendeskripsikan penggunaan social networks sites sebagai media pembelajaran dalam memfasilitasi pelajaran menulis bahasa Inggris di SMA dan SMK di Buleleng. Penelitian ini menggunakan pendekatan penelitian campuran. Pengumpulan data dilakukan dengan memberikan kuesioner, melakukan wawancara dan observasi. Responden dalam penelitian ini adalah 13 guru bahasa Inggris dari 11 sekolah dan juga 110 siswa dari seluruh sebelas sekolah. Data menunjukkan bahwa penggunaan social networks sites sangat bermanfaat bagi guru dan siswa. Hal itu ditunjukkan dari persepsi guru dan persepsi siswa terhadap pelaksanaan social networks sites dikategorikan dalam tinggi. Dapat disimpulkan bahwa guru dan siswa menggunakan berbagai macam social networks sites dalam pembelajaran menulis dan juga mempunyai persepsi yang tinggi terhadap penggunaan social networks sites.Kata Kunci : Social networks sites, Media Pembelajaran, Menulis Bahasa Inggris. Social networks sites are an online platforms that can be used to support teaching and learning process in this global era. This study aims at describing the use of social networks sites as teaching media in facilitating English writing lesson in senior high schools and vocational high schools in Buleleng. This study uses mix-methods approach. The data were collected by giving questionnaires, doing an interview and observation. The respondents in this study were 13 English teachers from 11 high schools also 110 students from the entire eleven schools. The data shows that the use of social networks sites is very beneficial for the teacher and students. Meanwhile, teacher and students’ perception toward the implementation of social networks sites is categorized in high category. It can be concluded that teachers and students use various social networks sites in writing lesson as well as they have high perception towards the implementation social networks sites.keyword : Social Networks Sites, Teaching Media, English Writing.